2019
DOI: 10.1177/1535370219846492
|View full text |Cite
|
Sign up to set email alerts
|

P2RX7 functions as a putative biomarker of gastric cancer and contributes to worse prognosis

Abstract: P2RX7 has a vital role in promoting proliferation and metastasis and is relevant to worse prognosis in multiple tumors. Nevertheless, P2RX7’s prognostic value and unambiguous effect in gastric cancer remain to be further explored. Our study showed that the expression of P2RX7 in human gastric tumor tissue ( n = 80) was significantly higher than that in normal human gastric tissue ( n = 20, different cohort). Abnormally high expression of P2RX7 was related to larger tumor size ( P = 0.0473), higher T stage ( P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 25 publications
2
13
0
Order By: Relevance
“…Considering these differences, our results of P2Y2R and P2X4R relative expression could provide an idea about the progression of gastric cancer. This relationship between P2Y2R and P2X4R gene expression remarks the potential of purinergic signaling as a prospective biomarker for gastric cancer progression, as similar studies have reported for P2X7R, whose overexpression is related to tumor size, metastatic potential, and overall survival in human colorectal and gastric cancer [41,42]. The opposite effects observed after P2Y2R or P2X4R activation can be explained by the different signaling pathways that these receptors can trigger: P2Y2R is a Gαq-coupled receptor that increases intracellular calcium and activates protein kinase C but also can activate other signaling pathways such as PI3K-Akt [43] or ERK1/2 phosphorylation via a protein kinase C (PKC)-dependent mechanism [44,45].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Considering these differences, our results of P2Y2R and P2X4R relative expression could provide an idea about the progression of gastric cancer. This relationship between P2Y2R and P2X4R gene expression remarks the potential of purinergic signaling as a prospective biomarker for gastric cancer progression, as similar studies have reported for P2X7R, whose overexpression is related to tumor size, metastatic potential, and overall survival in human colorectal and gastric cancer [41,42]. The opposite effects observed after P2Y2R or P2X4R activation can be explained by the different signaling pathways that these receptors can trigger: P2Y2R is a Gαq-coupled receptor that increases intracellular calcium and activates protein kinase C but also can activate other signaling pathways such as PI3K-Akt [43] or ERK1/2 phosphorylation via a protein kinase C (PKC)-dependent mechanism [44,45].…”
Section: Discussionsupporting
confidence: 77%
“…Interestingly, it has been reported in this work that the expression of P2Y6R is diminished in GC-derived cells and gastric tumors [ 52 ]. Another receptor that has been linked with GC is P2X7R, whose expression is increased in gastric tumors and associated with lower survival of GC patients [ 42 ]. Adenosine and ATP inhibit cell proliferation and induced apoptosis in lung cancer [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of COX-2 in MDA-MB-231 cells through upstream inhibition of the nuclear factor κB (NF-κB) signaling suppressed its invasiveness ( Kim et al, 2014 ). The p42/44 MAPK signaling is upstream of the NF-κB-mediated COX-2 expression ( Akundi et al, 2005 ), and has been shown to be activated following P2 receptor stimulation ( Parvathenani et al, 2003 ; Yang et al, 2004 ; Lili et al, 2019 ). Similarly, p38 MAPK is essential for COX-2 synthesis, either directly through downstream activation of transcription factors ( Fiebich et al, 2000 ; Akundi et al, 2005 ), or through stabilization of COX-2 mRNA post-transcription, thereby prolonging the effect of COX-2 or inflammation for a much longer period ( Lasa et al, 2000 ; Harper and Tyson-Capper, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additional studies published have revealed that the P2X7 receptor is highly correlated with the growth of cancers, including GC, when ATP acts as an extracellular messenger. 21,22 TCGA database results showed that P2X7 is clearly related to an unfavorable prognosis in GC patients (Figure S1B) and is highly expressed in tumor tissues of GC patients (Figure S1A). It has been proposed that ATP5B activated the FAK/ AKT/MMP2 pathway through ATP binding its receptor P2X7.…”
Section: Atp Activates the Fak/akt/mmp2 Signaling Pathway Through Its Receptor P2x7mentioning
confidence: 99%